Multifocal demyelinating motor neuropathy and hamartoma syndrome associated with a de novo PTEN mutation. (22nd May 2018) - Bansagi, Boglarka; Phan, Vietxuan; Baker, Mark R.; O'Sullivan, Julia; Jennings, Matthew J.; Whittaker, Roger G.; Müller, Juliane S.; Duff, Jennifer; Griffin, Helen; Miller, James A.L.; Gorman, Grainne S.; Lochmüller, Hanns; et al.
Abstract : Objective: To describe a patient with a multifocal demyelinating motor neuropathy with onset in childhood and a mutation in phosphatase and tensin homolog ( PTEN ), a tumor suppressor gene associated with inherited tumor susceptibility conditions, macrocephaly, autism, ataxia, tremor, and epilepsy. Functional implications of this protein have been investigated in Parkinson and Alzheimer diseases. Methods: We performed whole-exome sequencing in the patient's genomic DNA validated by Sanger sequencing. Immunoblotting, in vitro enzymatic assay, and label-free shotgun proteomic profiling were performed in the patient's fibroblasts. Results: The predominant clinical presentation of the patient was a childhood onset, asymmetric progressive multifocal motor neuropathy. In addition, he presented with macrocephaly, autism spectrum disorder, and skin hamartomas, considered as clinical criteria for PTEN-related hamartoma tumor syndrome. Extensive tumor screening did not detect any malignancies. We detected a novel de novo heterozygous c.269T>C, p.(Phe90Ser) PTEN variant, which was absent in both parents. The pathogenicity of the variant is supported by altered expression of several PTEN-associated proteins involved in tumorigenesis. Moreover, fibroblasts showed a defect in catalytic activity of PTEN against the secondary substrate, phosphatidylinositol 3, 4-trisphosphate. In support of our findings, focal hypermyelination leading to peripheral neuropathy has been reported in PTEN-deficient mice. Conclusion: We describe a novel phenotype, PTEN-associated multifocal demyelinating motor neuropathy with a skin hamartoma syndrome. A similar mechanism may potentially underlie other forms of Charcot-Marie-Tooth disease with involvement of the phosphatidylinositol pathway.